2023
DOI: 10.1039/d3tc01681a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric anthracene hosts decorated with naphthobenzofurocarbazole for highly efficient deep-blue organic light-emitting diodes and low-efficiency roll-off

Abstract: In this study, two anthracene hosts, 5-(4-(10-phenylanthracen-9-yl)phenyl)-5H-naphtho[2',3':4,5]furo[3,2-c]carbazole (ATPNF-1) and 5-(3-(10-phenylanthracen-9-yl)phenyl)-5H-naphtho[2',3':4,5]furo[3,2-c]carbazole (ATPNF-2), with napthobenzofurocarbazole (NBFC) unit, have been developed to perform as deep-blue emitters for high-efficiency non-doped OLEDs. These compounds exhibit...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…These TT pairs are weakly exchange-coupled, allowing the ratio of TT pairs to be varied by an external magnetic field. Among them, only the singlet-featured 1 (TT) can transition to the singlet state. In Figure c, the MEL of Device A1 exhibits a typical TTF MEL fingerprint, sharply increasing at low magnetic fields (<50 mT) and decreasing at high magnetic fields (>50 mT), as only MADN is involved in the emission process. , However, as shown in Figure d,e, the MEL of Device B1 and Device C1 exhibits a different pattern with a sharp increase up to low magnetic fields (∼50 mT) and a slight rise up to high magnetic fields, indicating the presence of an hRISC channel in the MEL fingerprint. In addition, the MEL intensity decreases with increasing voltage in the high magnetic field, which represents another MEL characteristic of TTF due to its electric-field-dependent process, ultimately confirming that the EEL device involves both the hRISC and TTF processes simultaneously. Comparably, Device B1 with PAC as the EEL exhibits a relatively less decrease in MEL in the high magnetic field region, which might be attributed to the higher contribution to EL by the hRISC channel in PAC.…”
Section: Resultsmentioning
confidence: 95%
“…These TT pairs are weakly exchange-coupled, allowing the ratio of TT pairs to be varied by an external magnetic field. Among them, only the singlet-featured 1 (TT) can transition to the singlet state. In Figure c, the MEL of Device A1 exhibits a typical TTF MEL fingerprint, sharply increasing at low magnetic fields (<50 mT) and decreasing at high magnetic fields (>50 mT), as only MADN is involved in the emission process. , However, as shown in Figure d,e, the MEL of Device B1 and Device C1 exhibits a different pattern with a sharp increase up to low magnetic fields (∼50 mT) and a slight rise up to high magnetic fields, indicating the presence of an hRISC channel in the MEL fingerprint. In addition, the MEL intensity decreases with increasing voltage in the high magnetic field, which represents another MEL characteristic of TTF due to its electric-field-dependent process, ultimately confirming that the EEL device involves both the hRISC and TTF processes simultaneously. Comparably, Device B1 with PAC as the EEL exhibits a relatively less decrease in MEL in the high magnetic field region, which might be attributed to the higher contribution to EL by the hRISC channel in PAC.…”
Section: Resultsmentioning
confidence: 95%
“…Here, TPA with electron-donating ability and TPE with AIE characteristics were substituted to maintain deep-blue emission with an asymmetric structure. In the case of compounds with asymmetric structures, intermolecular packing is effectively prevented in the film state, resulting in amorphous films and improved device stability [32][33][34]. The optical and electrical properties of synthesized blue chrysene derivatives were compared and analyzed.…”
Section: Molecular Design Synthesis and Characterization Of Organic B...mentioning
confidence: 99%
“…22 Benefiting from this unique advantage, hot exciton emitters are easier to design and can more easily realize deep-blue light than TADF emitters. 23 Previous studies have revealed that the T 2 state of anthracene is energetically close to its S 1 state, with a considerable T 2 –T 1 energy gap of 1.3 eV. 24 This distinctive arrangement of energy levels renders anthracene an excellent candidate for building a high-performing emitter of hot excitons.…”
Section: Introductionmentioning
confidence: 99%